Tilburg Teachers Trilogy - De Nooijer, Paul; Musser, King Jerry (The Netherlands, 1981)
Filmic research into the manipulation of time in film. At the end of the film, Mol shows his famous time-lapse pictures of budding flowers.
No Dialogue
Verzio Film Festival Submission
Keywords: Experimental films